Degraded Arid Soil Reclamation for Cotton Cultivation Using Organic Waste Amendments - Kogbara, Reginald; Kogbara,R.; Hamdi,H.; Al-Sharshani,A.; Abdalla,O.; Onwusogh,U.; Solim,S. (Springer Nature, 2024)
Qatar is one of the most fertilizer-dependent countries due to challenging soil and climatic conditions. The country strives toward self-sufficiency in agricultural production in alignment with the Qatar National Vision 2030. Hence, this work investigates the potential of utilizing nutrient-rich resources that are currently wasted for the reclamation of degraded arid soils to support the cultivation of industrial crops such as cotton (Gossypium spp.). Two abundant organic wastes, industrial biosludge and cow dung compost, were employed as soil amendments at a 3% application rate on a silty loam soil with relatively high salinity (electrical conductivity = 5.60 dS/m) and compared with conventional chemical fertilization. Cotton (May 344 variety) was then grown on the biowaste-amended soils in lysimeters for ten months (March through January) spanning through the hot season in Qatar, with the average temperature ranging from 19 to 37 °C. Soil properties and plant growth characteristics, including soil metal concentrations, days to germination and flowering, plant height, and cotton yield, were determined at set periods. The results indicated that different from the chemical fertilizer treatment, the organic amendments led to a significant release of potassium eight months after planting, roughly twice the concentration available at the initial sampling period. In all treatments, soil magnesium and iron concentrations generally increased, while phosphorus and zinc decreased over time. There was generally no significant difference in the concentrations of metals analyzed such as chromium, copper, nickel, and zinc between soils amended with the organic wastes and chemical fertilizer. The concentrations of metals were below the regulatory limits for sewage sludge applied to soils. The days to germination were 2, 9, and 11, while the days to flowering were 61, 92, and 77 for the cow dung compost, biosludge, and fertilizer treatments, respectively. The average cumulative plant heights were 74, 65, and 63 cm, while the average cumulative cotton boll yield was 7.3, 5.4, and 2.6 tons/ha, respectively, in the cow dung compost, biosludge, and fertilizer treatments. The results demonstrate that the organic amendments, especially cow dung compost, can help reclamation of degraded/saline arid soils under the described pedo-climatic conditions. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
Keywords: Cotton; Cow dung compost; Industrial biosludge; Organic waste amendments; Plant growth parameters